Directed evolution of recombinant C-terminal truncated lipase from Staphylococcus epidermidis AT2 for enhanced thermal stability - Veno, Jiivittha (2017)
Lipases specifically thermostable lipases which are origin from microbial are desirable commercially as they are resilient and robust. In the industrial processes, lipases are expected to operate at temperatures above 40°C and could retain activity in organic solvents. However, screening of organic tolerant lipases with increased thermal property from organisms is time consuming for high yield. Therefore, the objective of this study is to evolve rT-M386 lipase using error-prone PCR to achieve thermostability and to study the effect of mutation on biochemical properties and structural conformations of the lipase. In the first screening, approximately 1500 positive colonies were obtained. From these thousands of colonies, 900 colonies were analyzed quantitatively and resulted in seven mutant clones which exhibited higher activity when compared to rT-M386. Out of seven mutants, G210C lipase demonstrated a remarkable improvement of the activity by 5-fold when compared with rT-M386 at 50°C. rT-M386 and G210C were purified concurrently using GST-affinity chromatography with the yield of 92.25% and 92.17%, respectively. A distinct single band with a molecular weight of 69 kDa was observed on SDS-PAGE. The purified G210C lipase showed a 20°C increased of the optimum temperature. Apparently, rT-M386 could not maintain its stability for 30 min at temperatures above 20°C as its decreasing drastically. Meanwhile, G210C presented an exceptional thermal stability profile as it can sustain its stability at 50°C with 100% of relative activity. In addition, G210C lipase displayed more prolonged half-life in the range of 40-60°C as compared to rT-M386. Both lipases exhibited optimal activity and stability at pH 8. G210C exhibited the highest activity in the presence of diethyl ether, isopropanol, DMSO and methanol at 50ºC compared to rT-M386. Structural analysis of rT-M386 and G210C lipases has demonstrated variations in structural conformation. CD spectral analysis revealed that G210C attained more structural stability compared to the rT-M386 lipase and this supported the experimental findings. The structure was found more stable and compact as revealed by molecular dynamic simulation, suggesting its tolerance at elevated temperature. In conclusion, the results indicated that single residue substitution of G210C lipase contributes to the enhancement of thermal stability without adversely impacting the catalytic performance. rT-M386 lipase was successfully mutated via directed evolution strategy and the findings will be useful insight on the understanding of the structural-functional adaptation of thermostable lipases.